Upaya Meningkatkan Motivasi dan Hasil Belajar Siswa Melalui Penerapan Model Blended Learning Berbantuan Google Classroom pada Mata Pelajaran Dasar Kuliner - Made Mertha Dewini; I Gusti Ayu Agung Sinta Diarini; I Wayan Suryanto (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2022)
AbstractThis research aims to find out the increase of students’ motivation andlearning outcome in basic culinary subjects through blended learningmodel application that assisted by google classroom. The quantitativeanalysis technique used in this research is in the experimentalresearch design category and the sampling technique is purposivesampling. The research subject is all of the students in X class ofCulinary Art in SMKN 5 Denpasar totaling 40 people. The results ofthe pre-test of learning motivation obtained indicators of the need forachievement and affiliation of 78% and power of 73%. The pre-test ofcognitive domain learning outcomes showed a percentage of 80%,affective 81%, and psychomotor 79%. Through the application of theblended learning model, the results of an increase in the motivationalpost-test are the need for achievement by 79%, power and affiliationby 80%. Learning outcomes have increased, namely the cognitivedomain by 85%, affective 84% and psychomotor 82%. It concludedthat there is an increase in students' motivation and learning outcomesafter applying the blended learning model.AbstrakPenelitian ini memiliki tujuan yaitu mengetahui peningkatan motivasidan hasil belajar siswa pada mata pelajaran dasar kuliner melaluipenerapan model blended learning berbantuan google classroom.Teknik analisis kuantitatif yang digunakan dalam penelitian iniberkategori jenis penelitian eksperimen serta teknik sampling yaitupurposive sampling. Subjek yang diambil dalam penelitian ini yaknisemua siswa kelas X Tata Boga 1 SMKN 5 Denpasar yang berjumlah40 orang. Hasil pretest motivasi belajar memperoleh indikatorkebutuhan akan prestasi dan afiliasi sebesar 78% dan kekuasaansebesar 73%. Pretest hasil belajar ranah kognitif menunjukanpersentase sebesar 80%, afektif 81%, dan psikomotor 79%. Melaluipenerapan model blended learning, mendapatkan hasil peningkatanpada posttest motivasi yaitu kebutuhan akan prestasi sebesar 79%, kekuasaan dan afiliasi sebesar 80%. Hasil belajar mengalamipeningkatan yaitu ranah kognitif sebesar 85%, afektif 84% danpsikomotor 82%. Simpulan yang diperoleh adalah terjadi suatupeningkatan motivasi dan hasil belajar pada siswa setelah menerapkanmodel pembelajaran blended learning.